National bean variety trial - National Bean Programme (National Bean Programme, 1990)
Trials were carried out in 7 regions of Malawi (Chitipa, Rumphi, Mzuzu, Mzimba, Liliongwe, Dedza, and Thyolo) with 12 bean genotypes. In Dedza, yields varied from 1305 to 3204 kg/ha; genotypes 21-5, A286, A344, 25-2 x 8-7 gave significantly higher yields than genotypes 5-2, 25-2, and 25-2 x 8-7 as well as a greater no. of seeds/pod (4.0-5.3). Seed size of the assessed genotypes varied from 24.2 to 58.1 g/100 seeds. In Mzuzu, genotypes A286, A344, 29 x P692, Phalombe, and Nsaka gave significantly higher seed yields. CIAT genotypes A344 and A286 yielded significantly higher than the other genotypes (1140 and 1424 kg/ha, resp.); their superior performance was attributed to their degree of resistance to diseases such as angular leaf spot, CBB, floury leaf spot, and web blight. In Malawi, however, kidney beans are preferred; therefore the direct release of these genotypes should not be considered. They can be used instead as parental material. Promising var. of the Malawi germplasm collection were 2-10 x 8-7, 25-2 x 8-7, 8-7, and Phalombe. (CIAT)